PEMBERDAYAAN EKONOMI KREATIF MASYARAKAT DESA MANDALASARI KECAMATAN KADUHEJO KABUPATEN PANDEGLANG DALAM PEMANFAATAN LIMBAH BOTOL PLASTIC SEBAGAI MEDIA TANAM HYDROBOKAS - Abdul Bahits; Indah Rahayu; Nadya Khairunnisa; Rini Hernita; Erlangga Dwi Putra; Muhammad Reyhan Ferdiansyah (Yayasan Education and Social Center, 2026)
This Community Service Program (PkM) aimed to enhance the capacity of the community in Mandalasari Village, Kaduhejo District, Pandeglang Regency, by promoting the creative economy through the utilization of plastic bottle waste as Hydrobokas planting media. The primary issues identified were the low utilization of plastic waste and the limited public knowledge regarding waste management with economic value. The program employed the Participatory Rural Appraisal (PRA) approach, consisting of socialization, observation, training, demonstrations, hands-on practice, mentoring, and evaluation. The activities actively involved lecturers, university students, village officials, farmers, and local community members throughout all stages of implementation. The results demonstrated significant improvements in community knowledge regarding waste management based on the 3R principles (reduce, reuse, and recycle), enhanced participants' skills in independently producing Hydrobokas planting media, and increased public awareness of transforming plastic bottle waste into products with practical and economic value. In addition to contributing to environmental conservation through plastic waste reduction, the program created opportunities for developing creative economy-based microenterprises, strengthened household food security through home gardening, and fostered collaboration among universities, village governments, and local communities. Therefore, the Hydrobokas-based community empowerment model has strong potential to be replicated in other regions as a sustainable strategy for plastic waste management while supporting the implementation of a circular economy and sustainable rural development.